THE EFFECT OF PROJECT-BASED EDUCATION IN SCIENCE AND TECHNOLOGY LESSON ON THE SCIENTIFIC PROCESS SKILLS OF 4TH GRADE ELEMENTARY PUPILS - Mehtap YURDATAPAN (Fırat University, 2019)
The way of doing a project is a scientist’s way to access to knowledge or to form information. So to put the students into the project work means that they gain scientific process skills and use them. In this study, the effect of science projects undertaken by elementary pupils on the scientific process skills level was examined. The research was designed according to one of the experimental research models, pre-test post-test designs, with a control group experimental method. The study group of the research consists of a total of 33 pupils from the 4th grades of an elementary school in Kadikoy, Istanbul. A total of 6 project groups of primarily three in